Pelatihan Kegiatan Keselamatan dan Kesehatan Kerja bagi Mahasiswa Teknik Industri di PT Kemalir Prima Abadi - Heru Winarno; Andri Kapuji; M.Bob Antoni; Syaina Ulfah Azhara; Firyaliza Dwi Putri (Institut Nalanda, 2024)
Occupational Safety and Health (OHS) training is an important step in creating a safe and healthy work environment for all workers. This paper examines the implementation of OHS training in various industrial sectors and its impact on reducing work accidents and increasing worker awareness of workplace risks. This study uses a descriptive method with a qualitative and quantitative approach, involving workers and OHS managers in several companies. The results of the study indicate that effective OHS training can improve workers' understanding of safety procedures, strengthen OHS culture in the workplace, and reduce the number of accidents and occupational diseases. In addition, OHS training also plays an important role in complying with occupational safety regulations. Therefore, the development and improvement of the quality of OHS training on an ongoing basis are essential to achieve the goal of zero accidents and create a safer and healthier work environment. Occupational health and safety (OHS) training is well designed and implemented, as shown by the enthusiasm of students to participate in the activities and the responses of students who strongly agree with its implementation.